Unusual metastatic sex cord stromal tumor - staging and response assessment - Agrawal, Namita; Jain, Tarun Kumar; Singh, Guman; Malhotra, Hemant; Yadav, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Metastatic sex cord stromal tumor (SCST) is rare and contributing <1% of ovarian tumors. A 42-year-old female presented with lower abdominal pain for 2 months. Ultrasonography revealed masses in the abdominal and pelvic. USG guided biopsy from the pelvic mass revealed SCST. For staging, whole body F-18 fluorodeoxyglucose positron emission tomography-computed tomography was performed and revealed heterogenous mildly FDG avid retroperitoneal and bilateral pelvic masses with lung nodules. To confirm the nature of the lung nodule; PET-CT guided biopsy performed and revealed metastatic SCST. After three cycle of chemotherapy, clinical, biochemical and imaging show partial response to treatment.